Circulating microRNA expression profiles in pre-eclampsia: evidence of increased miR-885-5p levels - Sandrim, V. C.; Luizon, M. R.; Palei, A. C.; Tanus-Santos, J. E.; Cavalli, R. C. (Wiley, 2016)
OBJECTIVE: To validate and to compare the circulating microRNA (miR) expression profiles between pre-eclampsia and healthy pregnant women, to perform correlation analysis of the differently expressed miRs with clinical and biochemical parameters, and to verify the extracellular localisation of miRs in apoptotic bodies, microvesicles, and exosomes. DESIGN: A case-control study with a replication study. SETTING: Pregnant women attending maternity hospitals in Southeastern Brazil. POPULATION: Two obstetric white populations: a case-control study (19 pre-eclampsia and 14 healthy pregnant) and a replication study (eight pre-eclampsia and eight healthy pregnant). METHODS: PCR-array with 84 different miRs was performed in plasma from five pre-eclampsia and four healthy pregnant women. In the case-control study, differently expressed miRs were validated using quantitative real-time reverse transcription polymerase chain reaction (qRT-PCR), and correlated with clinical and biochemical parameters. The plasma was then fractioned to study the extracellular localisation of miRs. MAIN OUTCOME MEASURES: Gene expression profiles of miRs. RESULTS: From PCR-array, three miRs (miR-376c-3p, miR-19a-3p, and miR-19b-3p) were found to be down-regulated and the miR-885-5p was found to be up-regulated in pre-eclampsia compared with healthy pregnant women. In the validation step, miR-885-5p was the only significantly different miR (fold-change = 5.0, P < 0.05), which was confirmed in the replication study (fold-change = 4.5, P < 0.05). Moreover, miR-885-5p was significantly correlated with the hepatic enzyme aspartate transaminase (r = 0.66; P = 0.0034) and it was mostly associated with the exosomes (32-fold higher than apoptotic bodies). CONCLUSIONS: miR-885-5p is increased in plasma from pre-eclampsia compared with healthy pregnant women, and it is released into circulation mainly inside exosomes. TWEETABLE ABSTRACT: miR-885-5p is increased in pre-eclampsia and is released into circulation mainly inside exosomes.
Keywords: Circulating microRNAs; exosomes; miR-885-5p; pre-eclampsia